Dopant Site Environment and Spectrum Blue Shift of Yellow‐Emitting Solid Solution Phosphor Ba2−xSrxMg(PO4)2:Eu2+. Issue 2 (8th October 2015) - Hu, Qingsong; Pan, Zaifa; Xu, Yu; Wang, Lili; Ning, Lixin
Abstract : An unexpected spectrum blue shift of the yellow emission was observed for solid solution phosphors Ba2− x Sr x Mg(PO4 )2 :Eu 2+ ( x  = 0–1.5), when bigger ions Ba 2+ were substituted by smaller ions Sr 2+ in Ba2 Mg(PO4 )2 lattices. The solid solution phosphors were prepared by a solid‐state reaction to clarify the local sites environment of activators Eu 2+ and tune the anomalous long‐wavelength yellow emission. BaSrMg(PO4 )2 phase was identified to be isostructural with Ba2 Mg(PO4 )2 by Rietveld refinements. DFT calculation and photoluminescence show that the activator ions Eu 2+ in BaSrMg(PO4 )2 occupy Sr 2+ and Ba 2+ sites at an equal probability and both generate an anomalous yellow emission. The yellow emission from Ba2− x Sr x Mg(PO4 )2 :Eu 2+ was gradually blue shift with increasing Sr 2+ substitution concentration x from 0.1 to 1. Such unusual blue shift is interpreted based on the evolution of crystal structure parameters due to Sr 2+ substitution, and subsequently, a site environmental expansion mechanism is proposed. The proposed mechanism could serve as a general model to reveal the underlying factors for spectrum shift caused by cation substitution and contribute to design new solid solution phosphors.